Adaptive Autonomic and Neuroplastic Control in Diabetic Neuropathy: A Narrative Review - Marsili, Francesca; Potgieter, Paul; Birkill, Corlius F. (Current Diabetes Reviews, 2024)
Background: Type 2 diabetes mellitus (T2DM) is a worldwide socioeconomic burden, and is accompanied by a variety of metabolic disorders, as well as nerve dysfunction referred to as diabetic neuropathy (DN). Despite a tremendous body of research, the pathogenesis of DN remains largely elusive. Currently, two schools of thought exist regarding the pathogenesis of diabetic neuropathy: a) mitochondrial-induced toxicity, and b) microvascular damage. Both mechanisms signify DN as an intractable disease and, as a consequence, therapeutic approaches treat symptoms with limited efficacy and risk of side effects. Objective: Here, we propose that the human body exclusively employs mechanisms of adaptation to protect itself during an adverse event. For this purpose, two control systems are defined, namely the autonomic and the neural control systems. The autonomic control system responds via inflammatory and immune responses, while the neural control system regulates neural signaling, via plastic adaptation. Both systems are proposed to regulate a network of temporal and causative connections which unravel the complex nature of diabetic complications. Results: A significant result of this approach infers that both systems make DN reversible, thus opening the door to novel therapeutic applications.
Keywords: autonomic control system